A Novel Butanol Tolerance-Promoting Function of the Transcription Factor Rob in Escherichia coli - Wang, Zhiquan; Xue, Tingli; Hu, Dongsheng; Ma, Yuanyuan (Frontiers in Bioengineering and Biotechnology, 2020)
Producing high concentrations of biobutanol is challenging, primarily because of the toxicity of butanol toward cells. In our previous study, several butanol tolerance-promoting genes were identified from butanol-tolerant Escherichia coli mutants and inactivation of the transcriptional regulator factor Rob was shown to improve butanol tolerance. Here, the butanol tolerance characteristics and mechanism regulated by inactivated Rob are investigated. Comparative transcriptome analysis of strain DTrob, with a truncated rob in the genome, and the control BW25113 revealed 285 differentially expressed genes (DEGs) to be associated with butanol tolerance and categorized as having transport, localization, and oxidoreductase activities. Expression of 25 DEGs representing different functional categories was analyzed by quantitative reverse transcription PCR (qRT-PCR) to assess the reliability of the RNA-Seq data, and 92% of the genes showed the same expression trend. Based on functional complementation experiments of key DEGs, deletions of glgS and yibT increased the butanol tolerance of E. coli, whereas overexpression of fadB resulted in increased cell density and a slight increase in butanol tolerance. A metabolic network analysis of these DEGs revealed that six genes (fadA, fadB, fadD, fadL, poxB, and acs) associated with acetyl-CoA production were significantly upregulated in DTrob, suggesting that Rob inactivation might enhance butanol tolerance by increasing acetyl-CoA. Interestingly, DTrob produced more acetate in response to butanol stress than the wild-type strain, resulting in the upregulation expression of some genes involved in acetate metabolism. Altogether, the results of this study reveal the mechanism underlying increased butanol tolerance in E. coli regulated by Rob inactivation.